Health care expenses impact on the disability-adjusted life years in non-communicable diseases in the European Union - Torres, Margarida; Nunes, Alcina; Martins, João P.; Ferreira, Pedro L.; Pimenta, Rui (Frontiers in Public Health, 2024)
Background Non-communicable diseases are a global health problem. The metric Disability-Adjusted Life Years was developed to measure its impact on health systems. This metric makes it possible to understand a disease’s burden, towards defining healthcare policies. This research analysed the effect of healthcare expenditures in the evolution of disability-adjusted life years for non-communicable diseases in the European Union between 2000 and 2019. Methods Data were collected for all 27 European Union countries from Global Burden of Disease 2019, Global Health Expenditure, and EUROSTAT databases. Econometric panel data models were used to assess the impact of healthcare expenses on the disability-adjusted life years. Only models with a coefficient of determination equal to or higher than 10% were analysed. Results There was a decrease in the non-communicable diseases with the highest disability-adjusted life years: cardiovascular diseases (−2,952 years/105 inhabitants) and neoplasms (−618 years/105 inhabitants). Health expenditure significantly decreased disability-adjusted life years for all analysed diseases (p < 0.01) unless for musculoskeletal disorders. Private health expenditure did not show a significant effect on neurological and musculoskeletal disorders (p > 0.05) whereas public health expenditure did not significantly influence skin and subcutaneous diseases (p > 0.05). Conclusion Health expenditure have proved to be effective in the reduction of several diseases. However, some categories such as musculoskeletal and mental disorders must be a priority for health policies in the future since, despite their low mortality, they can present high morbidity and disability.